18F-FDG PET/CT in xanthogranulomatous cholecystitis with CA199 elevation: diagnostic dilemmas and differentiation strategies - Qi, Wanling; Chen, Min; Shao, Mingyan (Frontiers in Medicine, 2025)
ObjectiveXanthogranulomatous cholecystitis (XGC) is a rare and distinctive form of chronic cholecystitis, and it is rather challenging to differentiate it from the thick-walled type of gallbladder carcinoma. Considering that computed tomography (CT), magnetic resonance imaging (MRI), and 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) each exhibit unique features in the manifestation of XGC, this study aims to deepen the understanding of XGC and explore the roles of these imaging examinations, especially PET/CT, in the diagnosis and differential diagnosis of XGC.MethodsWe retrospectively analyzed the radiological, clinical, and surgical pathological data of five patients with XGC treated at Jiangxi Provincial People’s Hospital between January 2019 and January 2025.ResultsAll five patients with XGC were female, aged 49–84 years. Four patients were hospitalized for recurrent abdominal pain, while one presented with limb weakness. Carbohydrate antigen 19-9 (CA19-9) levels were elevated in three patients. Among the cases in this manuscript, one patient underwent contrast-enhanced MRI, two patients underwent contrast-enhanced CT, and all five patients underwent positron emission PET/CT examination. The results of the imaging examinations revealed that the gallbladder volume was enlarged in three cases and reduced in two cases. The gallbladder wall showed thickening to varying degrees (ranging approximately from 1.2 to 2.0 cm), with diffuse thickening observed in three cases and localized thickening in two cases. The enhancement pattern was characterized by progressive and sustained enhancement, and there was an increase in FDG uptake to different extents. Intramural nodules and gallstones were detected in three cases, and enlarged abdominal or retroperitoneal lymph nodes were found in two cases. The range of the maximum standardized uptake value (SUVmax) was between 7.5 and 19.8, and the median uptake value was 10.04 ± 5.75.ConclusionIn light of the insufficient diagnostic accuracy of FDG-PET/CT and CA 19-9 in distinguishing XGC from GBC, future efforts should prioritize the validation and adoption of advanced imaging techniques such as FLT-PET/CT. Pending these developments, radical cholecystectomy performed by experienced surgeons remains the recommended surgical strategy for suspected cases.